Implementasi Manajemen Kesiswaan di MA Al Islam Jamsaren Surakarta - Alfian Muchammad Zidane; Muhammad Wildan Shohib (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to determine the role of the vice principal of MA Al Islam Jamsaren Surakarta in his role in implementing student management along with the programs planned and implemented for the next one year. This study uses qualitative and descriptive analysis. Interviews, documentation, and observation the collected data. This study shows the role of the vice principal in implementing student management, namely planning one year, coordinating the implementation of PPDB, monitoring and supervising programs that have been implemented, receiving aspirations from each extracurricular related to infrastructure and fostering them, then also evaluating all the results of the programs that have been implemented for one year whether they are good or not. The programs that are often implemented by student affairs are camping, reading the Riyadhus Shalihin book, and implementing blood donation from the PMR madrasah. These programs provide real experiences for students that would not be possible to get in classroom learning.